Architectural design of multi-agent systems technologies and techniques - Lin 1965- (Information Science Reference, 2007)
"This book is a compilation of advanced research results in architecture and modeling issues of multi-agent systems. It serves as a reference for research on system models, architectural design languages, methods and reasoning, module interface design, and design issues"--Provided by publisher.